Phosphite protects against potato and tomato late blight in tropical climates and has varying toxicity depending on the Phytophthora infestans isolate. (July 2019) - Mulugeta, Tewodros; Abreha, Kibrom; Tekie, Habte; Mulatu, Bayeh; Yesuf, Mohammed; Andreasson, Erik; Liljeroth, Erland; Alexandersson, Erik
Abstract: Late blight caused by the oomycete Phytophthora infestans is one of the most severe diseases of potato ( Solanum tuberosum L.) and tomato ( Solanum lycopersicum L.). In this study, field trials were conducted in a cool tropical highland of Ethiopia for three consecutive years to investigate the efficacy of phosphite alone and in combination with conventional fungicide against late blight in two potato cultivars and one tomato cultivar. Phosphite alone and in combination with reduced dosages of the fungicide Ridomil Gold™ (mancozeb 64% and metalaxyl-M 4% (w/w)) led to effective suppression of late blight in research plots and in farmers' fields under light-to-normal late blight pressure. However, phosphite was not as effective as the fungicide under high disease pressure. Notably, phosphite was more effective against tomato late blight than against potato late blight, and gave the same protection as the fungicide in tomato. In vitro assays showed small differences in sensitivity to phosphite among five European and two Ethiopian isolates of P. infestans in terms of radial growth, sporangium production and sporangium germination, which could affect the population structure. Since phosphite can be provided at a lower price than conventional fungicides, it can reduce expenses for Ethiopian farmers with preserved late blight control. Highlights: Phosphite reduced late blight severity and increased yield in potato and tomato in tropical highlands under field conditions. Phosphite mixed with 25% of fungicide reduced late blight severity in potato and tomato as effectively as 100% fungicide. Different P. infestans isolates had varying tolerance to phosphite in vitro, which could affect population structures.